The nexus between urbanization and rural development in China: Evidence from panel data analysis - Li, Yuheng; Huang, Huiqian; Song, Chuanyao (Growth and change, 2022)
As rural decline sweeps the world and draws public attention, it becomes necessary to consider the relationship between urbanization and rural development. The paper investigates this topic in China for the period 1989–2018. The research results find positive contribution of urbanization to rural economy in the research period but with a decreasing tendency. Compared to less developed areas, rural economy of developed regions has become less dependent on cities and can flourish in a larger context with the support of modern transportation and telecommunication technologies. However, those peripheral rural areas tend to face continuous and large‐scale rural–urban migration which has aggravated rural decline. Rural economic growth helps to decrease rural outmigration and people will stay in their hometown with available job opportunities to raise their families and maintain livelihood. The paper proposes balance‐friendly urbanization structure and diversified rural economy to improve rural resilience to meet the challenge of rural decline.